2017
DOI: 10.1016/j.apenergy.2017.08.038
|View full text |Cite
|
Sign up to set email alerts
|

A novel stochastic modeling method to simulate cooling loads in residential districts

Abstract: District cooling systems are widely used in urban residential communities in China. Most district cooling systems are oversized; this leads to wasted investment and low operational efficiency and thus energy wastage. The accurate prediction of district cooling loads that supports rightsizing cooling plant equipment remains a challenge. This study developed a new stochastic modeling method that includes (1) six prototype house models representing a majority of apartments in the district, (2) occupant behavior m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(32 citation statements)
references
References 56 publications
(81 reference statements)
0
32
0
Order By: Relevance
“…It is for example well known that the maximal total power demand in a district is different from the sum of the individual buildings' maximal power demands [17]. For a case study in China An et al [18] demonstrated that oversimplified assumptions about occupant behavior leads to a significant overestimation of the peak cooling loads resulting in the design of oversized, inefficient district cooling systems.…”
Section: Key Challenges In Simulating On the Urban-scale Versus The Bmentioning
confidence: 99%
See 3 more Smart Citations
“…It is for example well known that the maximal total power demand in a district is different from the sum of the individual buildings' maximal power demands [17]. For a case study in China An et al [18] demonstrated that oversimplified assumptions about occupant behavior leads to a significant overestimation of the peak cooling loads resulting in the design of oversized, inefficient district cooling systems.…”
Section: Key Challenges In Simulating On the Urban-scale Versus The Bmentioning
confidence: 99%
“…The main concerns with occupant behavior on the urban-scale are the diversity among buildings of the same occupancy type, that should be accounted for to obtain realistic energy demand patterns [36,37] and the impacts of behavioral changes over time onto building energy demand [9]. Preliminary research on urban-scale occupant behavior models concludes that stochastic approaches, rather than deterministic, should be considered when high resolution temporal behavior and realistic peak loads are important [18,38,39]. On the other hand, for studies based on monthly or yearly energy consumption, the effect of human behavior might not be significant due to averaging effects [39].…”
Section: Occupant Behavior In Urban-scale Building Energy Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally speaking, a heat wave refers to a period of time with extremely hot weather. According to the WMO's Task Team on the Definition of Extreme Weather and Climate Events (TT-DEWCE), a heat wave should meet these conditions: (1) the weather is unusually hot and exceeds some given threshold; (2) the event lasts for at least two consecutive days; and (3) occurs during the hot period in one year (WMO, 2015). In different countries or regions, the indices used to define hot, thresholds and duration varies.…”
Section: Introductionmentioning
confidence: 99%